The static demand multipliers in a joint production framework: Comparative findings for the Greek, Spanish and Eurozone economies - Theodore Mariolis; Nikolaos Ntemiroglou; George Soklis (Journal of Economic Structures, 2018)
This paper uses input-output data from Supply and Use Tables for the year 2010 and provides empirical estimations of the static demand multipliers in a joint production framework for two representative Southern Eurozone economies, i.e., Greece and Spain, and for the Eurozone economy as a whole. The findings reveal certain differentiated features of the economies under consideration, call into question the post-2010 'horizontal' implementation of economic policy measures and, finally, provide a context for formulating well-targeted effective demand management and structural policy programs.
Keywords: C67; D57; E11; E12; E61; 330; Joint production; Management of effective demand; Matrix multipliers; Southern Eurozone economies; Supply and Use Tables